2019
DOI: 10.2147/jmdh.s196873
|View full text |Cite
|
Sign up to set email alerts
|

<p>Interprofessional communication in a sociohierarchical culture: development of the TRI-O guide</p>

Abstract: Objectives: Interprofessional education (IPE) and collaborative practice are essential for patient safety. Effective teamwork starting with partnership-based communications should be introduced early in the educational process. Many societies in the world hold socio-hierarchical culture with a wide power distance, which makes collaboration among health professionals challenging. Since an appropriate communication framework for this context is not yet available, this study filled that gap by developing a guide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
(119 reference statements)
0
18
0
2
Order By: Relevance
“…Interprofessional communication (IPC) is the liaison between different healthcare practitioners and the community to facilitate patient-centred care and patient safety, 1 and is integral to achieving coordinated patient care. Undeniably, communication failure between healthcare practitioners (HCPs) is recognised as a leading cause of avoidable patient harm.…”
Section: Introductionmentioning
confidence: 99%
“…Interprofessional communication (IPC) is the liaison between different healthcare practitioners and the community to facilitate patient-centred care and patient safety, 1 and is integral to achieving coordinated patient care. Undeniably, communication failure between healthcare practitioners (HCPs) is recognised as a leading cause of avoidable patient harm.…”
Section: Introductionmentioning
confidence: 99%
“…Support staffs in clinical areas include receptionists, secretaries and administrative clerks, who often communicate with patients. Hence the potentially poorer patient safety culture among this group of workers in a hospital setting highlights the need to work with this group of individuals, particularly as a previously published study conducted in the Netherlands reported more positive scores from administrative workers 32,33 …”
Section: Discussionmentioning
confidence: 93%
“…Hence the potentially poorer patient safety culture among this group of workers in a hospital setting highlights the need to work with this group of individuals, particularly as a previously published study conducted in the Netherlands reported more positive scores from administrative workers. 32,33 Stress recognition is an acknowledgement of how performance is persuaded by stressors. Apart from doctors, stress recognition scores were substantially lower than the acceptable threshold in the other professional groups, with the mean domain score for the overall study also below satisfactory levels.…”
Section: Ta B L E 1 Characteristic Of Respondentsmentioning
confidence: 99%
“…Nonetheless, there are also barriers of prominent professional boundaries and hierarchy that challenge the pathway implementation in primary care; and these barriers are not uncommon for any intervention implementation in health care settings [ 31 ]. However, the hierarchical barrier is very prominent in the Indonesian context, in which the study took place [ 32 , 33 ], outweighing other classical barriers of implementation in LMICs, such as limited clinical resources and facilities [ 34 , 35 ]. Nurses and midwives in Indonesia are usually positioned at a lower hierarchical level than GPs, and GPs often feel inferior to and less qualified than specialists [ 36 ].…”
Section: Discussionmentioning
confidence: 99%